Considering Human Milk Variability in the Nutritional Management of Low-Birth-Weight Infants. (October 2014) - Groh-Wargo, Sharon; Valentic, Jennifer; Khaira, Sharmeel; Super, Dennis M.; Collin, Marc
Human milk is the preferred feeding for babies but requires fortification to meet the needs of low-birth-weight infants. Human milk is known to vary with length of gestation and state of lactation. We describe the degree of variability both between mothers and within a mother's own milk supply in the setting of the neonatal intensive care unit. Aliquots from 24-hour supplies of human milk from mothers of infants weighing <2 kg at birth who were between 2 and 6 weeks of life were analyzed for lactose, bioavailable protein, and fat using a mid-infrared milk analyzer. Variability was estimated for each macronutrient by calculating the coefficient of variation (%) and was significantly less within one mother than between mothers ( P < .05). The variability in macronutrient content between mothers supports the use of human milk analysis when establishing a nutritional management plan for low-birth-weight infants. Low variability within a mother's own milk supply suggests that weekly analysis is sufficient to establish an individualized fortification plan.